2010
DOI: 10.1007/s11270-010-0557-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metals on Decolorization of Reactive Blue HERD by Comamonas sp. UVS

Abstract: Comamonas sp. UVS was able to decolorize Reactive Blue HERD (RBHERD) dye (50 mg L −1 ) within 6 h under static condition. The maximum dye concentration degraded was 1,200 mg L −1 within 210 h. A numerical simulation with the model gives an optimal value of 35.71±0.696 mg dye g −1 cell h −1 for maximum rate (V max ) and 112.35±0.34 mg L −1 for the Michaelis constant (K m ). Comamonas sp. UVS has capability of decolorization of RBHERD in the presence of Mg 2+ , Ca 2+ , Cd 2+ , and Zn 2+ , whereas decolorization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…e effluent-adapted strain of Acinetobacter has the potentiality for color removal, and strains of Acinetobacter and Pseudomonas exhibit chemical oxygen which demands removal actions [64,65]. Besides that, the Comamonas strain retains amazing reusability and endurance traits in continuous decolorization processes [66]. Additionally, the genus of Pseudomonas including Pseudomonas putida and Pseudomonas alcaligenes has a lot of metabolic diversity, many of which were capable of metabolizing different chemical contaminants [67].…”
Section: Isolation Screening and Identification Of MIX Culturementioning
confidence: 99%
“…e effluent-adapted strain of Acinetobacter has the potentiality for color removal, and strains of Acinetobacter and Pseudomonas exhibit chemical oxygen which demands removal actions [64,65]. Besides that, the Comamonas strain retains amazing reusability and endurance traits in continuous decolorization processes [66]. Additionally, the genus of Pseudomonas including Pseudomonas putida and Pseudomonas alcaligenes has a lot of metabolic diversity, many of which were capable of metabolizing different chemical contaminants [67].…”
Section: Isolation Screening and Identification Of MIX Culturementioning
confidence: 99%
“…Jadhav and co-workers reported that the activity of laccase, a type of copper-containing polyphenol oxidase, was observed using a cell-free extract and culture supernatant of Comamonas sp. UVS (Jadhav et al 2011). Laccase of Comamonas sp.…”
Section: Effects Of Metals On Dba Degradationmentioning
confidence: 99%
“…These results suggest that heavy metals addition in culture media may maintain, enhance or affect enzymatic pathways involved in the decolourization process depending on the metal nature (Jadhav et al . ). In case of Zn 2+ , decolourization of RB5 processed normally suggesting that Zn 2+ ions did not affect neither growth nor decolourization.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies suggested biotechnological approaches to overcome this threat using pure culture or consortia for single removal of dyes or heavy metals (Jadhav et al . ). Several bacterial strains such as Providencia sp ., Pseudomonas aeuroginosa, Acinetobacter junii, Enterobacter sp ., Citrobacter sp ., Brevibacillus laterosporus and Bacillus sp.…”
Section: Introductionmentioning
confidence: 97%